1997
DOI: 10.1023/a:1007497005152
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Serotyping (heat stable antigens) was performed on 398 strains of Campylobacter jejuni from faeces of human enteritis cases in England. Strains isolated over 12 months at three locations were heterogeneous with 33 HS serotypes represented. HS1 and HS4 complex were the predominant types (34% of all strains). The monthly strain frequency distributions were similar at the three locations. The late spring peak appeared to be associated with a rise in miscellaneous serotypes rather than with the emergence of any ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…No single sequence type was associated with the late spring seasonal rise in human campylobacteriosis, a finding consistent with that of a previous study in England that used serotyping ( 26 ). However, we have shown complex ST-45 to be significantly more prevalent during summer months in rural than in suburban areas.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…No single sequence type was associated with the late spring seasonal rise in human campylobacteriosis, a finding consistent with that of a previous study in England that used serotyping ( 26 ). However, we have shown complex ST-45 to be significantly more prevalent during summer months in rural than in suburban areas.…”
Section: Discussionsupporting
confidence: 89%
“…MLST has also provided conceptual advances in understanding the population biology and epidemiology of C. jejuni ( 25 ). Previous studies that used phenotypic strain characterization methods failed to establish source/host associations for particular phenotypes ( 26 ), but recent studies with MLST, including a study in NW England, suggest that a measure of host association may be distinguishable when this system is used ( 27 ). …”
mentioning
confidence: 99%
“…Our PFGE and AFLP data also support those reported in a previous study carried out on Finnish C. jejuni strains [38]. The genetic diversity of C. jejuni is well recognised and is attributed to a number of distinct phenomena, including genomic rearrangements and horizontal gene transfer [39]. A study carried out in England by Owen et al [39] showed that C. jejuni strains from human strains were highly diverse by PFGE analysis.…”
Section: Discussionsupporting
confidence: 89%
“…The genetic diversity of C. jejuni is well recognised and is attributed to a number of distinct phenomena, including genomic rearrangements and horizontal gene transfer [39]. A study carried out in England by Owen et al [39] showed that C. jejuni strains from human strains were highly diverse by PFGE analysis. Previous studies also described that MLST, AFLP, PFGE and DNA microarrays could not identify GBS-specific genetic markers by comparing the genomes of C. jejuni strains [16], [21], [25], [29].…”
Section: Discussionmentioning
confidence: 99%